PENGARUH SISTEM INFORMASI PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN (Studi Pada PT Hasjrat Abadi Manado) - Lapalelo, Beatrix (Sam Ratulangi University, 2015)
Abstract : This study aimed to determine the effect of the marketing information system on severaldimensions of marketing management such as quality of service, customer satisfaction and customerloyalty of PT Hasrat Abadi Manado engaged in motor vehicle maintenance services. In this study,using a quantitative method with regression analysis approach. The sample totaled 98 respondentsdefined by using the formula of Slovin. Data was collected using questionnaires, interviews andobservation.Results of the study indicate partially a significant difference between the marketinginformation system and job satisfaction, marketing information systems with customer satisfaction,service quality and customer satisfaction, customer satisfaction with customer loyalty. Simultaneously,marketing and information systems service quality effect on customer satisfaction and customerloyalty. However, the variable that has the strongest influence occurs between the variable qualityof service with customer satisfaction variables. Therefore, to maintain and even increase the marketshare of the company should improve the quality of services in a sustainable manner.Keywords : Marketing information systems, Quality of service, Customer Satisfaction, CustomerLoyalty